An assessment of irrigated rice cultivation with different crop establishment practices in Vietnam - Van Hung Nguyen; Stuart, Alexander M.; Thi My Phung Nguyen; Thi Minh Hieu Pham; Ngoc Phuong Thanh Nguyen; Pame, Anny Ruth P.; Sander, Björn Ole; Gummert, Martin; Singleton, Grant R. (Springer, 2022)
Overuse of seed and chemical inputs is a major constraint for sustainable rice production in Vietnam. In this study, two seasons of field trials were conducted to compare different crop establishment practices for rice production in the Mekong River Delta using environmental and economic sustainability performance indicators. The indicators including energy efficiency, agronomic use efficiency, net income, and greenhouse gas emissions (GHGEs) were quantified based on four treatments including manual broadcast-seeding, blower seeding, drum seeding, and mechanized transplanting. Across the four treatments, yields ranged from 7.3–7.5 Mg ha−1 and 6.2–6.8 Mg ha−1 in the Winter-Spring (WS) and Summer-Autumn (SA) seasons, respectively. In comparison with direct seeding methods, mechanized transplanting decreased the seed rate by 40%. It also led to a 30–40% reduction in pesticide use during the main crop season (WS). Mechanized transplanting required higher inputs, including machine depreciation and fuel consumption, but its net energy balance, net income and GHGE were at a similar level as the other non-mechanized planting practices. Mechanized transplanting is a technology package that should be promoted to improve the economic and environmental sustainability of lowland rice cultivation in the Mekong River Delta of Vietnam.